Rainfall Analysis to Determine the Potential of Rainwater Harvesting Site in Kuantan, Pahang - Nadiatul Adilah, Ahmad Abdul Ghani; Noor Asiah, Mohamad; Teo, Wei Hui (Asian Research Publishing Network (ARPN), 2016)
Malaysia as a country which received a very high rainfall throughout the year is moving towards adopting rainwater harvesting system (RWHS) as a means to mitigate water shortage and flood problem. In 2012, RWHS is made compulsory for every development of new housing and building at several states in Malaysia, both for water supply and flood control. Furthermore, since flood is becoming more prevalent nowadays in Malaysia especially in Kuantan, Pahang, lacks of space for the construction of flood mitigation facilities has prompted authorities to look for other solutions for flood control. This study intends to determine the potential of rainwater harvesting site in Kuantan, Pahang. Daily rainfall data from six selected hydrology stations in Kuantan catchment are used to analyse the water availability in order to identify the potential of rainwater harvesting site in Kuantan. The highest amount of rainfall received by all stations for five consecutive years is on December except for two stations recorded highest amount of rainfall on January in year 2011 and three stations recorded highest amount of rainfall on February and May in year 2013. Meanwhile the least number of rainfalls received by all stations for five consecutive years varies.